Scanning Electron Microscopic Examination of Rainbow Trout Gastrointestinal Mucosa - DEMİRCİ, Beste (Kastamonu Üniversitesi Veteriner Fakültesi, 2023)
Aim to study: The aim of this study was to determine the morphological characteristics of the gastrointestinal mucosa of the rainbow trout. Material and methods: This study was carried out on 10 rainbow trout's stomach and intestinal tissues using scanning electron microscope. In the study, 2.5% glutaraldehyde fixation and routine scanning electron microscopy procedures were applied. Results: The surface architecture of the gastrointestinal tract was examined in detail. It was observed that the mucosal folds in the stomach increased in number towards the pyloric region and were arranged in a configuration that allowed food to be directed to the intestine. The columnar cells of the digestive tract mucosa and the mucosal openings that allow mucus secretion were shown in detail. Conclusion: The gastrointestinal tract of trout, a carnivorous species, was studied in detail. The structure of the columnar cells, gastric glands and mucus openings of this system was revealed in three dimensions. The detailed anatomy of the mucosal surface, which is rapidly affected by food variation or pathological changes in fish, was revealed. This study will shed light on studies affecting the morphology of the digestive system.
Keywords: Veteriner Anatomi ve Fizyoloji; Intestine; rainbow trout; scanning electron microscopy; stomach.; Veterinary Anatomy and Physiology